How do you assess the Dynamics of Sustainable Business Operations during the COVID-19 Pandemic? - Mishra, Anjay Kumar (Journal of Advanced Research in HR and Organizational Management, 2021)
It is my pleasure to raise issues of HR and organization through this editorial which may be of assistance for you to further conduct your future research.